What do you mean? Nuclear stress in english as an international language: uses and interpretations - Reis, Leonice Passarella dos (2017)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2017.